Journalistic biography of José Ponce Bernal (Huelva 1898 – Madrid 1940) - Mendoza Ponce, Felicidad (Historia y Comunicación Social, 2016)
José Ponce Bernal (Huelva 1898 - Madrid 1940) was a Spanish journalist and politician, who lived in the first third of the 20th century. His life and work has recently been object of a doctoral thesis. He’s an example of a journalist, who saw in that job the suitable instrument to change society. Through his articles he wanted to influence the thinking of his contemporaries and decided to take political actions. He was an intellectual committed to society, who had to live in a time of social and political turmoil. His close link to left-wing politics was responsible for a tragic end after the Spanish civil-war.
Keywords: Journalism; II Republic; politics; civil war.